Effect of Gamma Irradiation on Regeneration Capacity of Mangosteen Nodular Callus - WARID ALI QOSIM; ROEDHY PURWANTO; GULDOF ALBERT WATTIMENA; WITJAKSONO WITJAKSONO (HAYATI Journal of Biosciences, 2007)
The research was conducted to determine the effect of gamma irradiation on regeneration capacity of mangosteed nodular callus. Nodular calli derived from a leaf as explants and cultured on MS medium containing combination of 2.2 µM benzilaminopurin (BAP) and 2.27 µM tidiazuron (TDZ). Nodular calli were irradiated with 0 (control) 5, 10, 15, 20, 25, 30, 35, and 40 Gy doses of gamma irradiation. After the irradiation, the calli were generated on woody plant medium (WPM), supplemented with 1.39 µM polyvinilpirolidon (PVP), 8 g.l-1 agar, 30 g.l-1 sucrose and 2.2 µM BAP concentration. Results showed that the irradiation influence the plant regeneration. Response dose of 50% (RD) that could promote the nodular calli of shoot formation was the 25 Gy while that of the shoot number per nodular calli was the 21 Gy. The shoot number irradiated with total dose 5 Gy (9.1 shoot) was higher than that of 0 Gy (8.6 shoot). Key words: plant regeneration, irradiation gamma rays, mangosteen